ANALISA SWOT STRATEGI PEMASARAN DAN KEPUASAN PELANGGAN DI PERUSAHAAN ALFAMART BOYOLALI (Studi Kasus Alfamart Jl. Pandanaran No.194, Banaran, Kecamatan Boyolali, Kabupaten Boyolali) - Mar'atus Sholikhatul Ummah; Listyowati Puji Rahayu; Unna Ria Safitri; Hari Purwanto (EKOBIS, 2024)
This study aims to determine and improve the right marketing strategy, as well as the relationship between the level of customer satisfaction and marketing strategy and SWOT analysis at Alfamart Boyolali. The method used in this research is qualitative, namely research that emphasizes the analysis more on the process of deductive and inductive inferences on the dynamics of the observed phenomena using scientific logic. The data used is the result of distributing questionnaires to strengthen the results of the analysis as well as conducting surveys, problem identification, literature study, identification of research variables, validity testing and data analysis. The results of the research are data analysis from interviews with resource persons and distributing questionnaires which include Internal environmental analysis including discussions of company strengths and weaknesses which include company management based on POAC, marketing based on 5P, research, development and information systems used. External Environmental Analysis on micro-relationships between suppliers and well established. Customer satisfaction based on the questionnaire that was analyzed got the highest results on the opportunity variable with an average of 44.4, the strength variable with an average of 33.85 and the weakness variable got an average of 38.24. The comparison becomes a problem because the weakness is greater than the strength, so to achieve maximum strength, it is necessary to increase or change.